Effects of Merino Wool on Atopic Dermatitis Using Clinical, Quality of Life, and Physiological Outcome Measures - Fowler, Joseph F. (Dermatitis, 2019)
BACKGROUND: Wool clothing may be perceived as a poor choice for use by individuals with sensitive skin or atopic dermatitis. OBJECTIVES: The aims of the study were to evaluate the effect on atopic dermatitis of wearing fine Merino wool clothing versus standard clothing and to assess the effect of Merino wool clothing on quality of life in children and adults with atopic dermatitis 5 years and older. METHODS: Subjects with mild to moderate atopic dermatitis were assessed in a crossover fashion after wearing Merino wool clothing for 6 weeks and standard clothing for 6 weeks, for Eczema Area and Severity Index, Dermatology Life Quality Index, static Investigator's Global Assessment, and skin hydration. RESULTS: While wearing Merino wool clothing, compared with standard clothing, statistically significant improvements were seen in mean Eczema Area and Severity Index scores, Dermatology Life Quality Index scores, and static Investigator's Global Assessment scores. No significant difference was seen with skin hydration. Wearing Merino wool clothing did not produce any negative cutaneous effects compared with wearing standard clothing. CONCLUSIONS: Merino wool clothing compared with standard clothing provided improvements in severity of atopic dermatitis as well as quality of life in atopic patients.